2007
DOI: 10.1016/j.ijgo.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Twin chorionicity and the risk of adverse perinatal outcome

Abstract: The incidence of neonatal complications was higher in MC twins born of pregnancies complicated by TTS or sIUGR. Although the incidence of sIUGR was similar in MC and DC pregnancies, there was a trend towards worse outcomes in MC pregnancies affected by sIUGR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
149
2
14

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(169 citation statements)
references
References 23 publications
4
149
2
14
Order By: Relevance
“…Glinianaia et al [12] also reported that MC twins have higher SRs compared with MZ Di Chorionic (DC) twins in England during the period 1998-2007. Increased stillbirth risk in MC compared with DC twins are mainly attributed to twin-twin transfusion syndrome (TTTS) [13][14][15][16]. According to Morikawa et al [17], Japanese women with MC diamniotic twins were 2.2-fold more likely to experience stillbirth than women with DC diamniotic twins during the period [2005][2006][2007][2008].In the present study, 14% of FDs in MZ twins were attributable to TTTS.…”
Section: Discussionmentioning
confidence: 58%
“…Glinianaia et al [12] also reported that MC twins have higher SRs compared with MZ Di Chorionic (DC) twins in England during the period 1998-2007. Increased stillbirth risk in MC compared with DC twins are mainly attributed to twin-twin transfusion syndrome (TTTS) [13][14][15][16]. According to Morikawa et al [17], Japanese women with MC diamniotic twins were 2.2-fold more likely to experience stillbirth than women with DC diamniotic twins during the period [2005][2006][2007][2008].In the present study, 14% of FDs in MZ twins were attributable to TTTS.…”
Section: Discussionmentioning
confidence: 58%
“…An MC pregnancy with sIUGR was defined as a combination of the co-twin with an estimated fetal weight below the 10th percentile and fetal weight discordance between the twin pair >25% (Acosta-Rojas et al, 2007;Ananth et al, 1998). Intermittent UA-AEDF is not recognized as abnormal Doppler in this study.…”
Section: Methodsmentioning
confidence: 99%
“…But the etiology of betamethasoneinduced return of positive end-diastolic UA flow is unclear (Robertson et al, 2009). Selective intrauterine growth restriction (sIUGR) occurs in about 12% of monochorionic twin (MC) pregnancies (Gaziano et al, 2000;Gratacos et al, 2004;Sebire et al, 1997); MC twins have a higher incidence of respiratory and neurological complications than their dichorionic counterparts (Acosta-Rojas et al, 2007;Fick et al, 2006;Gonzalez-Quintero et al, 2003). Antenatal corticosteroids are often administered to enhance fetal lung maturity due to the frequent need for delivery earlier than 34 weeks of gestation in order to avoid the intrauterine fetal demise of the sIUGR twin, which could subsequently lead to brain injury of the co-twin arising from agonal transfusion (Russell et al, 2007).…”
mentioning
confidence: 99%
“…1,11,17 A STFF foi documentada em 11,1% das gestações MC, o que está de acordo com o reportado por outros centros. [10][11][12]16,17,22 À semelhança do que foi descrito por outro estudo português 1 , encontrou-se uma maior incidência de cesariana na gravidez MC.…”
Section: 13unclassified
“…1,2,[6][7][8]13 Vários estudos têm demonstrado taxas de morbilidade e mortalidade mais elevadas nos gé-meos monocoriónicos comparativamente com os bicorióni-cos. 1,4,9,16 Isto pode ser explicado pela ocorrência frequente de anastomoses vasculares entre os fetos e de inserção anómala do cordão umbilical e pela partilha muitas vezes desigual da placenta, fatores responsáveis pela síndrome de transfusão feto-fetal (STFF), restrição de crescimento intra-uterino (RCIU) e crescimento fetal discordante (CFD), com potenciais consequências nefastas para ambos os fetos. 4,[11][12][13]16,17 Os objetivos deste trabalho foram: caracterizar a população de gémeos fruto de gravidez bifetal nascidos num hospital nível três e avaliar o impacto da corionicidade na morbimortalidade perinatal.…”
Section: Introductionunclassified